2018
DOI: 10.1038/s41598-018-19788-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiogenesis by leflunomide via targeting the soluble ephrin-A1/EphA2 system in bladder cancer

Abstract: Angiogenesis plays an important role in bladder cancer (BCa). The immunosuppressive drug leflunomide has attracted worldwide attention. However, the effects of leflunomide on angiogenesis in cancer remain unclear. Here, we report the increased expression of soluble ephrin-A1 (sEphrin-A1) in supernatants of BCa cell lines (RT4, T24, and TCCSUP) co-cultured with human umbilical vein endothelial cells (HUVECs) compared with that in immortalized uroepithelial cells (SV-HUC-1) co-cultured with HUVECs. sEphrin-A1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…9 A recent study showed the anti-angiogenesis effect of leflunomide on bladder cancer. 21 In the present study, we demonstrated that leflunomide reduced bladder cancer cell viability via inducing apoptosis and cell cycle arrest. Additionally, autophagy and Akt/mTOR signaling pathway were involved in the cytotoxicity of leflunomide on bladder cancer cells.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…9 A recent study showed the anti-angiogenesis effect of leflunomide on bladder cancer. 21 In the present study, we demonstrated that leflunomide reduced bladder cancer cell viability via inducing apoptosis and cell cycle arrest. Additionally, autophagy and Akt/mTOR signaling pathway were involved in the cytotoxicity of leflunomide on bladder cancer cells.…”
Section: Introductionsupporting
confidence: 51%
“…Recently, leflunomide was reported to inhibit tumor angiogenesis by suppressing ephrin-A1/EphA2 in bladder cancer. 21 However, other pathways affected by leflunomide such as apoptosis and autophagy mechanism in bladder cancer have not been well elucidated. In this study, we reported that leflunomide suppressed bladder cancer cells growth via inducing tumor cell apoptosis and cell cycle arrest in S phase.…”
Section: Discussionmentioning
confidence: 99%
“…Ephrin A1 is the ligand for EPHA receptors and is overexpressed in gastric cancer. In addition, soluble Ephrin A1 has been reported to be secreted in conditioned media of several cancer cell lines and be detected in serum of cancer patients [38][39][40]. We found that soluble Ephrin A1 was present in conditioned media of AGS and MKN cells Nine patients presented with metastatic disease.…”
Section: Impacts Of C1galt1 On Ephrin A1-triggered Phosphorylation Ofmentioning
confidence: 70%
“…Soluble Ephrin A1 can promote metastasis in several cancer types [38,39,42]. We found that C1GALT1 modified O-glycans on EPHA2 and regulated EPHA2 phosphorylation.…”
Section: C1galt1 Mediates Its Pro-migratory Effect On Gastric Cancer mentioning
confidence: 78%
“…Therefore, roles of EphB4 and ephrin‐B2 in tumor growth and agiogenesis are still controversial. In pathological conditions, EphA1/A2 and ephrin‐A1 have been implicated in tumor angiogenesis that is important for tumor growth to supply O 2 and nutrients . However, the detailed molecular mechanisms remain to be elucidated.…”
Section: Roles Of the Eph/ephrin System In Tumor Angiogenesismentioning
confidence: 99%